GANGGUAN KEAMANAN DALAM MASYARAKAT PASCA KEBERADAAN JALAN LINTAS SUMATERA DI JORONG GANTIANG KECAMATAN SIJUNJUNG KABUPATEN SIJUNJUNG - LINI, OKTA - (Pendidikan Sosiologi, 2014)
Development, in general, is a process of planned change from a domestic situation that the national situation to others who scored higher. As the development has a negative impact on society, such as road construction in Trans Sumatera Jorong Gantiang Kecamatan Sijunjung Kabupaten Sijunjung. The purpose of this study is to describe the causes of the disturbances to the community after the construction of the Trans Sumatera in Jorong Gantiang and describe a community effort so that no more security problems after the construction of the Trans Sumatera in Jorong Gantiang. Reality in this study were analyzed with the theory of social change. This research used a qualitative approach with descriptive type. Type a descriptive study seeks to explain and describe phenomena certain. Techniques taking informant by purposive sampling. Criteria informants, namely people whove been or lived before and after the Sumatera highway renovation in Jorong Gantiang, 15 informer number of people. This type of data is the primary data. Data was collected by observation, interview and documentation. The unit of analysis is the group with Miles & Huberman data analysis comprising the steps of reduction, data presentation / analysis of data, and drawing conclusions. Results of the study revealed that a security breach since the construction of the Trans Sumatera in Jorong Gantiang occur due to several causes including negligence of society, societys ignorance of the abandoned house in an empty state and the absence of the control or supervision of public figures (head Jorong and police). To cope with such cases the community has to patrol or siskamling in turns every night, people also perform a prime position on the provision that they fear.